Measurement Invariance in the Alabama Parenting Questionnaire: Implications for Culturally Inclusive Parenting Research. (August 2022) - Shaffer, Anne; Rodriguez, Violeta J.; Kolko, David J.; Pilkonis, Paul A.; Lindhiem, Oliver
Questions persist in the parenting literature regarding how best to define positive and negative parenting behaviors. Are there optimal parenting behaviors shared by mothers and fathers, or among different racial and ethnic groups? This study draws from a nationally representative sample of US parents of school-age children, testing aspects of measurement invariance in the Alabama Parenting Questionnaire (APQ) full and short forms. Our goal was to highlight psychometric approaches to enhancing cultural sensitivity and inclusivity in parenting research, by assessing whether self-reported parenting behaviors have similar conceptual structure across groups. Tests of measurement invariance revealed that the factor structure of the APQ was the same across parent gender, race, and ethnicity. While partial invariance was found in some instances, we did not find metric and scalar invariance in comparisons among these groups. We conclude with research- and practice-based implications, and provide recommendations for future measurement development and use.